Automated railway track switching system : A smart rail station control system - Khan, Md. Mohaiminul Islam (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.